Optimization and analysis of high gain wideband microstrip patch antenna using genetic algorithm - Gaurav Mishra, Raj; Mishra, Ranjan; Kuchhal, Piyush; Prasanthi Kumari, N. (International Journal of Engineering and Technology, 2017)
Microstrip antennas that can operate in single and multiple frequency bands are required in various wireless communication devices. A single patch, square shaped microstrip patch antenna having high directivity and gain is proposed in this paper. The geometry of proposed antenna is optimized using Genetic Algorithm (GA) to operate in X-Band for wideband applications. The proposed antenna design exhibits a wide operating bandwidth 550 MHz (simulated) and 450 MHz (measured), high gain and directivity of about 8.35 dB (simulated) making it suitable for wideband applications. The proposed antenna design works in X-band which has weatherproof characteristics and supports easy communication of voice, data, images and HD videos. The attractiveness of the GA design over the traditional design methods is its ability to achieve the desired performance by using a simple design of single patch antenna.